53 stitches : sustainability, ecology and social engagement in contemporary art - Salton, Bronwen Lauren (Rhodes University, Faculty of Humanities, Department of Fine Art, 2013)
Through an exploration of both the sculptural and socially-engaged art practices undertaken in creating my Master of Fine Art exhibition, 53 Stitches, I unpack some of the possibilities pertaining to the practice of sustainability, ecology and social engagement in contemporary art. This thesis explores the history and concepts of sustainable development and what the implications are of the far-reaching global consideration of sustainability for contemporary art production. Looking at the writings of Felix Guattari's (2000 [1989]) and Suzi Gablik's (1992) on the effects of the economic model of capitalism on our environmental, social and mental ecologies, I discuss the necessary paradigm shift of the artists' identity from the 'individual self' towards the 'relational self', affirming our interdependence upon our social and natural environments. With reference to the writings of Maja and Reuben Fowkes (2008), I explore the principles of sustainability in contemporary art and discuss the notion of 'sustainability of form' through insight into dematerialisation, recycling and the prospect of artists now becoming knowledge producers/facilitators. This is supportive of my personal exploration and experimentation with recyclable materials as a creative medium, used as a means of knowledge and skills facilitation in socially-engaged arts practice and the process of art-making as research. I refer to the sculptural and 'painterly' constructions of Sofi Zezmer and Mbongeni Buthelezi, respectively, as a means to elucidate a practical contextualisation of my practical work, particularly with regard to the use of plastic as a constructive medium. Looking at the works of Linda Weintraub (2006), Marnie Badham (2010) and Miwon Kwon (2002), I expand on the theoretical discourse pertaining to sociallyengaged art practices, and elucidate the reconfiguration of the role of the artist towards now becoming a cultural service administrator, organiser and knowledge facilitator. With reference to Arjen Wals and Johnson et al., I further discuss the role of education in sustainability and explore the necessary reconciliation between university institutions and the social and environmental context in which they are located, in the form of place-based capacity building and service learning. I explore within this thesis the concepts and processbased research of my own sculptures
Keywords: Crocheting; Community development -- South Africa; Ecology in art